SOLAR AND WIND ENERGY FOR SHIP POWER SYSTEM, CURRENT STATUS AND FUTURE PROSPECT - Diah Zakiah; Vidya Selasdini (Jurnal Maritim Malahayati, 2023)
The issue of climate change due to the greenhouse effect encourages various parties to try reducing emissions in energy fulfilment. In maritime sector, IMO has adopted mandatory measures to reduce emissions of greenhouse gases (GHG) from international shipping, under IMO's pollution prevention treaty (MARPOL). Besides Carbon Oxides (COX), statistics show that other exhaust emissions from ships, such as Sulfur Oxides(SOX), Nitrogen Oxides(NOX) and Particulate Matters(PM) have also increased significantly in the past years due to the rapid increase of the maritime transportation. It is necessary for the shipping industries to find out the available clear energy to reduce the emission of GHG. This paper will discuss application of solar and wind energy on ship power systems, current status and future prospect.